Clinical Comparison of the Performance of Two Marketed Ophthalmic Viscoelastic Devices (OVDs): The Bacterially Derived Healon PRO OVD and Animal-Derived Healon OVD. (18th November 2020) - Daas, Loay; Larrosa, Jose Manuel; Gavin, Alicia; Isanta, Carlos; Langenbucher, Achim; Jackson, Beth E.; Tsai, Linda; Janakiraman, Priya; Guerrero, Rafael; Seitz, Berthold
Abstract : This clinical investigation compared the clinical performance of two marketed ophthalmic viscoelastic devices (OVDs): the bacterially derived Healon PRO OVD (test) and the animal-derived Healon OVD (control) under normal use conditions during cataract removal and lens implantation. This prospective, multicenter, randomized, parallel, participant/evaluator masked, postmarket investigation enrolled 139 subjects (170 eyes), 116 (143 eyes) of which were treated (73 test; 70 control group). Both test and control OVDs were used, at a minimum, to inflate the anterior chamber and protect the endothelium prior to cataract extraction according to the standard procedure. The surgeon completed a postsurgery OVD clinical performance questionnaire, and intraocular pressure (IOP) was measured before surgery and at the 1 day postoperative visit with Goldmann applanation tonometry. Any IOP measurement of 30 mmHg or higher was considered a "spike" and recorded as a study-specific, serious adverse event. The bacterially derived Healon PRO OVD was found to be statistically noninferior to the overall clinical performance of the animal-derived Healon OVD control; thus, the primary hypothesis was satisfied. There were no statistically significant differences between OVD groups for any of the additional endpoints relating to IOP changes or to safety, thus satisfying additional hypotheses. The Healon PRO OVD showed statistically significant improvements in surgeon ratings for ease of injectability, transparency/visibility, and ease of IOL placement. The safety profile was also similar between OVD groups with regards to serious and/or device-related adverse events, as well as medical and lens findings. The results of this clinical investigation support the safety and effectiveness of the bacterially derived, currently marketed Healon PRO OVD and indicate that the intraocular surgical performance was similar between the two OVDs.